2020
DOI: 10.3390/jpm10040284
|View full text |Cite
|
Sign up to set email alerts
|

Whole Body 3.0 T Magnetic Resonance Imaging in Lymphomas: Comparison of Different Sequence Combinations for Staging Hodgkin’s and Diffuse Large B Cell Lymphomas

Abstract: To investigate the diagnostic value of different whole-body magnetic resonance imaging (WB-MRI) protocols for staging Hodgkin and diffuse-large B-cell lymphomas (HL and DLBCL), twenty-two patients (M/F 12/10, median age 32, range 22–87, HL/DLBCL 14/8) underwent baseline WB-MRI and 18F-2-fluoro-2-deoxy-D-glucose (18F-FDG) positron emission tomography (PET) fused with computed tomography (CT) scan 18F-FDG-PET-CT. The 3.0 T WB-MRI was performed using pre-contrast modified Dixon (mDixon), T2-weighted turbo-spin-ec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…The most commonly used morphological sequences were the STIR followed by T2 and T1 performed under free breathing, with breath-hold or respiratory-triggered. In one study (21) only, patients were given contrast material i.v. Occasionally, special acquisitions were performed for the neck and lungs (Table 2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The most commonly used morphological sequences were the STIR followed by T2 and T1 performed under free breathing, with breath-hold or respiratory-triggered. In one study (21) only, patients were given contrast material i.v. Occasionally, special acquisitions were performed for the neck and lungs (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…Most studies (n=11) reported agreement in the principal stages, one study (22) included E and S modifiers, where present. A single study (21) that reported agreement based on the Lugano criteria, was not included. A leave-one-out sensitivity analysis is shown on Figure S10.…”
Section: Resultsmentioning
confidence: 99%
“…They found that WB-MRI with diffusion-weighted imaging had a sensitivity of 94% for the detection of the aforementioned diseases, which was statistically significantly higher than the 88% sensitivity of WB-MRI without DWI [33]. The primary conclusion of the study was that "WB-MRI All," which combined all sequences, had the highest sensitivity and specificity for the assessment of lymphoma when comparing to PET-CT, by 100% [34]. Further review of this publication is beyond the scope of this manuscript; however, the study contains additional details that may be of interest to the reader.…”
Section: Magnetic Resonance Imagingmentioning
confidence: 98%
“…Several studies have reported significantly lower ADC values in lymphomas compared with normal lymph nodes and nodal sites of carcinoma [ 14 ]; moreover, ADC values increase after treatment in responder patients [ 15 , 16 ]. To date, however, WB-MRI is still not routinely performed in patients with lymphoma because of the absence of standardized parameters for assessing disease burden and degree of response to treatment, compared with 18F-FDG-PET/CT [ 17 ].…”
Section: Introductionmentioning
confidence: 99%